Вплив термічної обробки модифікованих киснем багатошарових вуглецевих нанотрубок на їхні електронні характеристики - Senkevich, A. I.; Koval's'ka, E. O.; Brichka, S. Ya.; Brichka, A. V.; Kartel, M. T. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
Researches of influence of oxygen chemisorption’s on spectral characteristics of multiwall carbon nanotubes are spent by method of X-ray spectroscopy. By means of the temperature-programming desorbtion with mass-spectrometry control gaseous products that are allocated at heating the synthesized samples are investigated.